PENGARUH TEAM GAMES TOURNAMENT BERMUATAN PEMBELAJARAN MENDALAM TERHADAP PEMAHAMAN KONSEP IPAS SISWA SD - Komang Dian Ariani; Ni Nyoman Kurniawati; I Gede Arya Wiradnyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Conceptual understanding in Integrated Science and Social Studies (IPAS) is one of the essential competencies emphasized in the Merdeka Curriculum. However, classroom instruction in elementary schools is still predominantly teacher-centered, limiting students' active engagement and conceptual understanding. This study aimed to examine the effect of the Team Games Tournament (TGT) model integrated with Deep Learning on elementary school students' conceptual understanding of IPAS. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The research involved 60 fifth-grade students from elementary schools in Cluster VII, Buleleng District, Indonesia. The sample consisted of 32 students in the experimental group and 28 students in the control group, selected through cluster random sampling. Data were collected using a conceptual understanding test that had met validity and reliability requirements. The data were analyzed using descriptive and inferential statistics, including normality, homogeneity, normalized gain (N-Gain), and the Independent Samples t-test. The results revealed that the experimental group's mean score increased from 66.16 to 93.97, with an N-Gain of 0.80 (84%), categorized as effective, whereas the control group's mean score increased from 58.39 to 71.93, with an N-Gain of 0.30 (31%), categorized as ineffective. Hypothesis testing indicated a statistically significant difference between the two groups (p < 0.05). These findings demonstrate that the Team Games Tournament model integrated with Deep Learning significantly improves elementary school students' conceptual understanding of IPAS. The study suggests that combining cooperative learning with deep learning principles provides more active, collaborative, and meaningful learning experiences and can serve as an effective instructional alternative for implementing the Merdeka Curriculum. Kata kunci: Team Games Tournament, Deep Learning, conceptual understanding, IPAS, elementary school.